Effects of methimepip and JNJ-5207852 in Wistar rats exposed to an open-field with and without object and in Balb/c mice exposed to a radial-arm maze - Ennaceur, Abdel; ABUHAMDAH, Rushdie M.; Lethbridge, Natasha L.; Chazot, Paul L.; van Rensburg, Ruan (Frontiers in Systems Neuroscience, 2012)
The role of the histamine H3 receptor (H3R) in anxiety is controversial, due to limitations in drug selectivity and limited validity of behavioral tests used in previous studies. In the present report, we describe two experiments. In the first one, Wistar rats were treated with an H3R agonist (methimepip), and exposed to an open-field. In the second one, Balb/c mice were treated with H3R agonist (methimepip) or antagonist (JNJ-5207852), and exposed to an open space 3D maze which is a modified version of the radial-arm maze. C57BL/6J saline treated mice were included for comparisons. When exposed to an empty open field, Wistar rats spent more time in the outer area and made very low number of brief crossings in the central area. However, when an object occupied the central area, rats crossed frequently into and spent a long time in the central area. Administration of a range of different doses of methimepip (selective H3R agonist) reduced the entries into the central area with a novel object, indicating enhanced avoidance response. In the 3D maze, both Balb/c and C57BL/6J saline-treated mice crossed frequently onto the bridges that radiate from the central platform but only C57BL/6J mice crossed onto the arms which extend the bridges. This suggests that Balb/c mice are more anxious than C57BL/6J mice. Neither methimepip nor JNJ-5207852 (selective H3R antagonist/inverse agonist) induced entry into the arms of the maze, indicative of lack of anxiolytic effects.